Rebooting Philippine telecommunications through structural reform - Ma. Kristina P. Ortiz; Ramonette B. Serafica; Jose Carlos Alexis C. Bairan (Philippine Institute for Development Studies (PIDS), 2017)
The quality of the Philippine telecommunication/information and communication technology (ICT) regulatory environment is significantly below what is considered international best practice. Using a scoring system developed by the International Telecommunication Union (ITU), where 100 points represent the best possible scenario, the Philippines is only midway toward the ideal with a score of 52.50. This is the second lowest in a group of seven ASEAN members. A package of structural reforms is needed to improve regulatory quality and support the efficient functioning of ICT markets. While the regulatory regime (or specific rules) and the competition framework are essential elements, they will only work if an effective regulatory authority with the right mandate is in place. Therefore, this should be prioritized in the reform agenda. Last but not least, universal access/service is an important goal that needs to be pursued. We should learn from our own and other countries' experience in crafting a new strategy.
Keywords: 330; telecommunications; ICT; broadband services; regulatory environment; structural reform